2002
DOI: 10.1016/s0022-5347(05)65290-1
|View full text |Cite
|
Sign up to set email alerts
|

The Bta Stat Test Is Nonspecific for Hematuria: An Experimental Hematuria Model

Abstract: The results of the BTA stat test in the presence of microscopic hematuria must be interpreted in regard to the degree of hematuria. The test is not reliable in urine samples with gross hematuria due to a high false-positive rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Hematuria severely affected the specificity of the BTAsta [9] and NMP22 [8, 31] detection and increased the false-positive results. We used the same methods of spiking urine specimens with whole blood as described previously [8, 9, 31], and found that hematuria did not affect the specificity of the SNCG ELISA detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematuria severely affected the specificity of the BTAsta [9] and NMP22 [8, 31] detection and increased the false-positive results. We used the same methods of spiking urine specimens with whole blood as described previously [8, 9, 31], and found that hematuria did not affect the specificity of the SNCG ELISA detection.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same methods of spiking urine specimens with whole blood as described previously [8, 9, 31], and found that hematuria did not affect the specificity of the SNCG ELISA detection. This finding was further supported by the absence of a correlation between the urine levels of SNCG and Hb-α or Hb-β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BTA tests (BTA stat™ and BTA TRAK™ (Polymedco Inc. Cortlandt Manor, NY, USA) have diagnostic sensitivities ranging from 29-83% and specificities ranging from 56-86% [3,4]. In addition, we and others have demonstrated in an experimental model that hematuria adversely affects the accuracy of the BTA assay [5,6]. The NMP-22 tests (NMP22® Bladder Cancer ELISA Test Kit and the NMP22® BladderChek® point-of-care test, Alere Scarborough, Inc. Waltham, MA) have diagnostic sensitivities ranging from 47-100% and specificities ranging from 55-98% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For BCa detection, urinary BTA tests have diagnostic sensitivities ranging from 29–83% and specificities ranging from 56–86% [4,5]. Recently, Oge et al demonstrated that hematuria adversely affects the accuracy of BTA assays [6]. …”
Section: Introductionmentioning
confidence: 99%